Endothelial progenitor cells and circulating endothelial cells in heart failure: a cross-sectional study - Lopes, José Carlos Martins (2022)
The objective of the present thesis was to compare the levels of circulating endothelial progenitor cells (EPCs), circulating endothelial cells (CECs), and hematopoietic stem cells (HSCs) between patients with heart failure with reduced ejection fraction (HFrEF) and a group of subjects with cardiovascular risk factors. We also compared the levels of circulating EPCs, CECs, and HSCs between subgroups regarding the presence of cardiovascular risk factors (e.g. diabetes mellitus) and the etiology of heart failure (HF). To achieved this, whole peripheral blood was drawn from patients previously diagnosed with HFrEF (n = 42) and age-matched subjects presenting similar cardiovascular risk factors but without established cardiovascular disease (n = 42). Then, a combination of markers was used in peripheral blood samples in order to assess the number of circulating EPCs, CECs, and HSCs via flow cytometry analysis. Patients with HFrEF had significantly decreased levels of circulating EPCs (5.28 x 10-3 ± 6.83 x 10-4 % vs 7.76 x 10-3 ± 4.91 x 10-4 %, P ≤ 0.001) and CECs (5.11 x 10-3 ± 7.87 x 10-4 % vs 6.51 x 10-3 ± 5.21 x 10-4 %, P = 0.005) compared to subjects with cardiovascular risk factors. However, levels of HSCs were not significantly different between the two groups (P = 0.590). Additionally, CECs (6.69 x 10-3 ± 6.38 x 10-3 % vs 3.61 x 10-3 ± 2.71 x 10-3 %, P = 0.057) tended to circulate in higher number in patients with ischemic HF compared to patients with non-ischemic HF. Patients with HFrEF and diagnosed as overweight/obese had significantly higher levels of circulating EPCs (6.10 x 10-3 ± 4.78 x 10-3 % vs 4.13 x 10-3 ± 3.55 x 10-3 %, P = 0.043) and CECs (6.27 x 10-3 ± 5.66 x 10-3 % vs 3.47 x 10-3 ± 3.54 x 10-3 %, P = 0.019) when compared to patients with HFrEF presenting a normal weight. Lastly, when comparing subjects from the age-matched group, subjects with dyslipidemia had significantly higher levels of CECs (7.74 x 10-3 ± 3.64 x 10-3 % vs 5.34 x 10-3 ± 2.59 x 10-3 %, P = 0.042) compared to subjects without dyslipidemia. In conclusion, the main result of this study is that the circulating levels of EPCs and CECs were significantly decreased in patients with HFrEF in comparison to subjects with cardiovascular risk factors. The current observations regarding cardiovascular risk factors suggest that EPCs, CECs, and HSCs play an important role in the detection and repair of vascular damage and endothelial dysfunction.